Concurrency Theory Calculi an Automata for Modelling Untimed and Timed Concurrent Systems - Bowman, Howard; Gomez, Rodolfo (Springer London : Imprint: Springer, 2006)
Concurrency Theory is a synthesis of one of the major threads of theoretical computer science research focusing on languages and graphical notations for describing collections of simultaneously evolving components that interact through synchronous communication. The main specification notation focused on in this book is LOTOS. An extensive introduction to this particular process calculus is given, highlighting how the approach differs from competitor techniques, such as CCS and CSP. The book covers linear-time semantics, based on traces; branching-time semantics, using both labeled transition systems and refusals; and true concurrency semantics, using (bundle) event structures. In addition, the book discusses communicating automata approaches (both finite and infinite state); how the theory can be generalised to the timed setting; and, finally, the authors generalise the (finite and infinite state) communicating automata notations to yield timed automata and discrete timed automata. This book represents a comprehensive pass through the spectrum of concurrency theory research: From untimed to timed syntax and semantics and process calculi to automata. Researchers and practitioners in the field of concurrency theory, as well as MSc and PhD students, will find the comprehensive coverage in this book essential reading.